Lipoprotein ontology: a formal representation of Lipoproteins - Kohn, Meifania Monica (Curtin University, 2013)
Lipoproteins serve as a mode of transport for the uptake, storage and metabolism of lipids. Dysregulation in lipoprotein metabolism, known as dyslipidaemia, is strongly correlated to various diseases such as cardiovascular disease. Lipoprotein Ontology provides a formal representation of lipoprotein concepts and relationships that can be used to support the intelligent retrieval of information, faciliate collaboration between research groups, and provide the basis for the development of tools for the diagnosis and treatment of dyslipidaemia.